« Amor mi paixs » : Langage biblique, enchantement et personnages redoublés dans la novas « Frayre de joy et sor de plaser » - Majorossy, Imre Gábor (Verbum – Analecta Neolatina, 2006)
This study deals with a so far not too often analysed old Provençal short story, which is a particular version of Sleeping Beauty. After an analysis of biblical vocabulary background and a presentation of various hidden oppositions in the novas, the paper focuses on the meaning of the speaking names, on the miracles and on the duplicated persons. As the second young couple plays a crucial role in the plot, it is necessary to find its identity and comprehensive literary function. The study concludes affirming that the short story shows the decline of fin'amor by a charming mixture of Christian, antique and popular beliefs. Among the three, it is the third that prevails, as the magic herb seems strong enough to wake up the dead princess. Even though the fin'amors ideology is still present, it is not predominating any more and cannot resolve the greatest human tragedy.